Analysis of inextensible sheet reinforcement subject to downward displacement/force: non-linear subgrade response. Issue 3 (1st June 2003) - Madhav, M. R.; Umashankar, B.
Abstract : Geosynthetic materials used to reinforce earth fills, ground and slopes resist the destabilising forces by mobilising tensile forces in the reinforcement. In most studies, only the pullout resistance due to axial pull is considered in stability analysis. However, the kinematics of failure clearly establish that the reinforcement is displaced obliquely. In this paper, a novel approach is presented for the analysis of sheet reinforcement subjected to transverse force or displacement. Assuming a non-linear subgrade/fill response and an inextensible reinforcement, the resistance to transverse displacement is estimated. The response to the applied force is shown to depend not only on the interface shear characteristics of the reinforcement but also on the deformational response of the ground. The unique feature of this study is the coupling of normal displacements with pullout response. A relation is established between pullout resistance and transverse free end displacement. A parametric study quantifies the effect of soil and interface characteristics of reinforcement on the overall response.